Biological mechanisms of growth performance and meat quality in porcine muscle tissue. Issue 6 (18th November 2022) - Fang, Chen; Guo, Fei; Zhao, Xiaoqi; Zhang, Zining; Lu, Junlan; Pan, Hongbin; Xu, Taojie; Li, Weizhen; Yang, Minghua; Huang, Ying; Zhao, Yanguang; Zhao, Sumei
Abstract: Growth performance and meat quality are important traits for pig production. The aim of the present study was to investigate the molecular mechanisms underlying growth performance and meat quality, and to identify novel target molecules for predicting the growth performance and meat quality. The differentially expressed genes (DEGs) in Diannan small ears pigs (DSP) and Landrace pigs (LP) were assessed by RNA-sequencing analyzing technology. A total of 339 DEGs were obtained between DSP and LP. 146 DEGs were upregulated in LP compared with DSP and 193 DEGs were upregulated in DSP compared with LP. The DEGs were significantly enriched in 26 GO and 3 KEGG pathways. The protein–protein interaction (PPI) network with 201 nodes and 382 edges was constructed and 5 modules were extracted from the entire network. The identified upregulated expression of genes involved in glycolysis and myogenesis as well as extracellular matrix may be associated with fast body and muscle deposition rates in LP. Increased expression of genes involved in PPAR signaling pathway and fatty acid metabolism as well as oxidative phosphate processes could be related to the intramuscular fat deposition and meat quality in DSP. The present study may provide an improved understanding of the growth performance and meat quality.